EQUILIBRIUM DENSITY AND EXPANSIVITY OF SILICATE MELTS IN THE GLASS TRANSITION RANGE - Toplis M.J.; Richet P. (My University, 2000)
Equilibrium volumes and expansivities of three liquids in the system anorthite (CaAl2Si2O8)-diopside (CaMgSi2O6) have been derived from dilatometric measurements of the equilibrium length of samples in the glass transition range. The typical temperature range of 40 K for the measurements is limited at low temperature by the very long times necessary to reach structural equilibrium and at high temperature by the penetration of the rod used to measure sample dilatation. Despite such narrow intervals, the expansivities are determined to better than 3% thanks to the high precision with which length changes are measured. The coefficient of volume thermal expansion (1/V dV/dT) of the fully relaxed liquid just above the glass transition is found to decrease linearly from diopside composition (139 ± 4 × 10-6 K-1) to anorthite composition (59 ± 2 × 10-6 K-1). These values are greater than those determined for the same liquids at superliquidus temperatures, demonstrating that expansivities of silicate melts may decrease markedly with increasing temperature. A predictive model based upon partial molar volumes which vary as a linear function of the logarithm of temperature is proposed.